Theoretical analysis of Brownian and thermophoresis motion effects for Newtonian fluid flow over nonlinear stretching cylinder. (December 2021) - Shafey, A.M. EI; Alharbi, Fahad M.; Javed, Aneela; Abbas, Nadeem; ALrafai, H.A.; Nadeem, S.; Issakhov, Alibek
Abstract: The Brownian and thermophoresis motion effects for the Newtonain nanofluid over a nonlinear stretching cylinder is taken into account in this analysis. The stagnation flow with chemical reaction effects analyzed for Newtonain nanofluid model. Flow is taken along the axial direction and developed the boundary layer approximation. Under the flow assumptions, mathematical model developed through Navier Stoke equations by means of boundary layer approximations. The developed model in terms of partial differential equations achieved by using the boundary layer approximations on the Navier Stoke equations. Furthermore, partial differential equations transformed into ordinary differential equations after applying the similarity variable. The achieved ordinary differential equations are solved through numerical procedure namely bvp4c technique. The results are achieved after solving the differential equations and involing physical parameters effects are presented in term of tabular as well as graphicals. By increasing prandtl number as well as the thermal boundary layer thickness decreases. Effect of R e which improve the velocity field and decrease the temperature and concentration profile.